Integrating Whole Blood Transcriptomic Collection Procedures Into the Current Anti-Doping Testing System, Including Long-Term Storage and Re-Testing of Anti-Doping Samples - Lima, Giscard; Kolliari-Turner, Alexander; Malinsky, Fernanda Rossell; Guppy, Fergus M.; Martin, Renan Paulo; Wang, Guan; Voss, Sven Christian; Georgakopoulos, Costas; Borrione, Paolo; Pigozzi, Fabio; Pitsiladis, Yannis (Frontiers in Molecular Biosciences, 2021)
Introduction: Recombinant human erythropoietin (rHuEPO) administration studies involving transcriptomic approaches have demonstrated a gene expression signature that could aid blood doping detection. However, current anti-doping testing does not involve collecting whole blood into tubes with RNA preservative. This study investigated if whole blood in long-term storage and whole blood left over from standard hematological testing in short-term storage could be used for transcriptomic analysis despite lacking RNA preservation. Methods: Whole blood samples were collected from twelve and fourteen healthy nonathletic males, for long-term and short-term storage experiments. Long-term storage involved whole blood collected into Tempus™ tubes and K2EDTA tubes and subjected to long-term (i.e., ‒80°C) storage and RNA extracted. Short-term storage involved whole blood collected into K2EDTA tubes and stored at 4°C for 6‒48 h and then incubated at room temperature for 1 and 2 h prior to addition of RNA preservative. RNA quantity, purity, and integrity were analyzed in addition to RNA-Seq using the MGI DNBSEQ-G400 on RNA from both the short- and long-term storage studies. Genes presenting a fold change (FC) of >1.1 or < ‒1.1 with p ≤ 0.05 for each comparison were considered differentially expressed. Microarray analysis using the Affymetrix GeneChip® Human Transcriptome 2.0 Array was additionally conducted on RNA from the short-term study with a false discovery ratio (FDR) of ≤0.05 and an FC of >1.1 or < ‒1.1 applied to identify differentially expressed genes. Results: RNA quantity, purity, and integrity from whole blood subjected to short- and long-term storage were sufficient for gene expression analysis. Long-term storage: when comparing blood tubes with and without RNA preservation 4,058 transcripts (6% of coding and non-coding transcripts) were differentially expressed using microarray and 658 genes (3.4% of mapped genes) were differentially expressed using RNA-Seq. Short-term storage: mean RNA integrity and yield were not significantly different at any of the time points. RNA-Seq analysis revealed a very small number of differentially expressed genes (70 or 1.37% of mapped genes) when comparing samples stored between 6 and 48 h without RNA preservative. None of the genes previously identified in rHuEPO administration studies were differently expressed in either long- or short-term storage experiments. Conclusion: RNA quantity, purity, and integrity were not significantly compromised from short- or long-term storage in blood storage tubes lacking RNA stabilization, indicating that transcriptomic analysis could be conducted using anti-doping samples collected or biobanked without RNA preservation.